2020
DOI: 10.1016/j.cpr.2020.101875
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenology of gender dysphoria in adults: A systematic review and meta-synthesis

Abstract: Gender dysphoria is distress due to a discrepancy between one's assigned gender and gender identity. Adults who wish to access gender clinics are assessed to ensure they meet the diagnostic criteria for gender dysphoria. Therefore, the definition of gender dysphoria has a significant impact on the lives of individuals who wish to undergo physical gender transition. This systematic review aimed to identify and synthesize all existing qualitative research literature about the lived experience of gender dysphoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 53 publications
(57 reference statements)
2
72
0
8
Order By: Relevance
“…In a non-trivial proportion, therapy has had limited success as evidenced by the high heterogeneity in quality of life outcomes across studies ( Murad et al, 2010 , Nobili et al, 2018 ), as well as variable improvements in body image ( van de Grift et al, 2016b , van de Grift et al, 2017 ). This may be due to inter-individual biological variability, contributions from sociological or cultural factors, or a combination of these factors ( Cooper et al, 2020 ). The desired therapy outcome is improved congruence between one’s gender identify and the sex-related physical characteristics of one’s body.…”
Section: Introductionmentioning
confidence: 99%
“…In a non-trivial proportion, therapy has had limited success as evidenced by the high heterogeneity in quality of life outcomes across studies ( Murad et al, 2010 , Nobili et al, 2018 ), as well as variable improvements in body image ( van de Grift et al, 2016b , van de Grift et al, 2017 ). This may be due to inter-individual biological variability, contributions from sociological or cultural factors, or a combination of these factors ( Cooper et al, 2020 ). The desired therapy outcome is improved congruence between one’s gender identify and the sex-related physical characteristics of one’s body.…”
Section: Introductionmentioning
confidence: 99%
“…is likely to arise from gender dysphoria, given the gender-body incongruence that gets "in the way" during sex (Doorduin & van Berlo, 2014), and might affect components of the SSC such as anxiety and esteem. Indeed, it has been shown that transgender individuals reported disappointment and depressive feelings related to the mismatch between their body and gender identity (Cooper et al, 2020), as would be predicted by the theory about self-concept discrepancies (Higgins et al, 1994). This mismatch and the related distress become less prominent after transition (Cooper et al, 2020), indicating that the discrepancy between the actual and ideal self-concept might decrease as transgender individuals transition toward their experienced gender.…”
Section: Introductionmentioning
confidence: 90%
“…Body dysphoria and conflicting feelings between body and identity are central themes in transgender experiences (Cooper et al, 2020), although not in all (Fiani & Heather, 2019). Because being comfortable with one's own body is an important aspect of sexual wellbeing (e.g., Sanchez & Kiefer, 2007), and sexual wellbeing is related to general happiness (Rosen & Bachman, 2008), it is important to investigate bodily selfperceptions in transgender persons (or self-related body perceptions) in relation to their sexual experiences.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is crucial to underline that the size of the transgender population does not reflect the true number of people with GD, as these terms are not identical. 4 Hence, the transgender population can only vaguely hint at the true number of people with GD.…”
Section: Epidemiology Of Gd In the Populationmentioning
confidence: 99%
“…Recent data indicate a percentage as high as 1%. 4 Concerning GD, it is estimated that 1% of the population experiences some level of discomfort and/or incongruence regarding their gender (https://www. bma.org.uk/advice-and-support/gp-pra ctices/gp-service-provision/managingpatients-with-gender-dysphoria).…”
Section: Epidemiological Data Of Gd In Adultsmentioning
confidence: 99%